Feasibility Study of Synthetic Diffusion-Weighted MRI in Patients with Breast Cancer in Comparison with Conventional Diffusion-Weighted MRI - Choi, Bo Hwa (Korean J Radiol, 2020)
OBJECTIVE: To investigate the clinical feasibility of synthetic diffusion-weighted imaging (sDWI) at different b-values in patients with breast cancer by assessing the diagnostic image quality and the quantitative measurements compared with conventional diffusion-weighted imaging (cDWI). MATERIALS AND METHODS: Fifty patients with breast cancer were assessed using cDWI at b-values of 800 and 1500 s/mm(2) (cDWI(800) and cDWI(1500)) and sDWI at b-values of 1000 and 1500 s/mm(2) (sDWI(1000) and sDWI(1500)). Qualitative analysis (normal glandular tissue suppression, overall image quality, and lesion conspicuity) was performed using a 4-point Likert-scale for all DWI sets and the cancer detection rate (CDR) was calculated. We also evaluated cancer-to-parenchyma contrast ratios for each DWI set in 45 patients with the lesion identified on any of the DWI sets. Statistical comparisons were performed using Friedman test, one-way analysis of variance, and Cochran's Q test. RESULTS: All parameters of qualitative analysis, cancer-to-parenchyma contrast ratios, and CDR increased with increasing b-values, regardless of the type of imaging (synthetic or conventional) (p < 0.001). Additionally, sDWI(1500) provided better lesion conspicuity than cDWI(1500) (3.52 ± 0.92 vs. 3.39 ± 0.90, p < 0.05). Although cDWI(1500) showed better normal glandular tissue suppression and overall image quality than sDWI(1500) (3.66 ± 0.78 and 3.73 ± 0.62 vs. 3.32 ± 0.90 and 3.35 ± 0.81, respectively; p < 0.05), there was no significant difference in their CDR (90.0%). Cancer-to-parenchyma contrast ratios were greater in sDWI(1500) than in cDWI(1500) (0.63 ± 0.17 vs. 0.55 ± 0.18, p < 0.001). CONCLUSION: sDWI(1500) can be feasible for evaluating breast cancers in clinical practice. It provides higher tumor conspicuity, better cancer-to-parenchyma contrast ratio, and comparable CDR when compared with cDWI(1500).